IMPROVING THE SCIENTIFIC AND METHODOLOGICAL FRAMEWORK FOR IMPROVING THE EFFECTIVENESS OF RECLAMATION MEASURES IN AGRICULTURE - Umurzakov, Uktam Pardaevich; Fayzullaevich, Sultanov Bahodir; Abdazovna, Adilova Guzal (International Journal of Psychosocial Rehabilitation, 2020)
–The article evaluates the role of land reclamation in the sustainable development of agricultural production on the basis of proposals and practical recommendations for improving the scientific and methodological framework for assessing and increasing the effectiveness of land reclamation in agriculture and the study of the economic nature of land reclamation and its scientific and practical basis. ; generalization of experience of foreign countries on increase of efficiency of ameliorative measures and development of practical offers on its application in economy of the republic, preparation of offers on improvement of methodical bases of use of ameliorative systems and an estimation of efficiency of actions, scientific assessment of impact of land reclamation on crop yield and product quality development of proposals to improve the methodological framework, structural and quantitative use of land and water resources and their benefits assessment of trends in changes in field efficiency, development of scientific proposals and practical recommendations on the classification, systematization and classification of measures to improve the reclamation of agricultural lands, the dynamics of the use of existing irrigation and land reclamation potential, assessment of its current state; Methodological recommendations for improving the scientific and practical basis for identifying areas of interaction between land reclamation and the environment and ensuring balance If the development explained.Substantiation of the priorities of preferential financial support of the state and innovative management of agricultural land reclamation in a market economy. Development of additional lands and prevention of the possible ecological crisis and effective use of arable lands. there is a need to ensure a balance between reproduction and economic activity of people on the basis of innovative solutions . The role of land reclamation as one of the factors of intensification of agricultural production is high and plays a primary and basic role in ensuring the efficiency of the sector, because, firstly, the lack of land reclamation limits the potential efficiency of the sector, and secondly, quantitatively and qualitatively leads to the cultivation of non-responsive products. development of proposals and practical recommendations to improve the scientific and methodological framework for assessing and increasing the effectiveness of reclamation measures in agriculture, which does not pay enough attention to the problems of improving the effectiveness of reclamation measures and a comprehensive study of this problem.